Implementasi Teori Belajar Kognitif Terhadap Minat Belajar Matematika - Mahmudah, Indri; Maemonah, Maemonah; Rahmaniar, Erita (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2022)
Currently, many students still complain that it is difficult to concentrate while studying. Especially in mathematics, the majority of students consider it a difficult subject. This research aims: 1) is there any effect of implementing cognitive learning theory to increase interest in learning in mathematics subjects, 2) how to implement cognitive theory to increase interest in learning in subjects mathematics, 3) knowing the weaknesses and strengths of implementing cognitive learning theory. This research uses a qualitative approach. Data collection techniques using documentation, interviews, and observations. The research subject involved one teacher, namely the homeroom teacher, three homeroom teachers, and fifteen VD grade students at SD Negeri 23 Palembang. The sample is determined by purposive. Sampling is a technique that is determined from a certain point of view. The results of this research show that there is a large influence on the implementation of cognitive learning theory so that it can increase students' interest in learning, especially in learning mathematics, as indicated by the enthusiasm of students during the learning process of mathematics subjects. students look active, tend to listen and then take notes on what the teacher says or explains so that learning goes well and most students ask questions, students can know and understand the subject matter that students must master.